Retrospective Multicenter Long-Term Follow-up Analysis of Prognostic Risk Factors for Recurrence-Free, Metastasis-Free, Cancer-Specific, and Overall Survival After Curative Nephrectomy in Non-metastatic Renal Cell Carcinoma - Kim, Sung Han; Park, Boram; Hwang, Eu Chang; Hong, Sung-Hoo; Jeong, Chang Wook; Kwak, Cheol; Byun, Seok Soo; Chung, Jinsoo (Frontiers in Oncology, 2019)
We evaluated prognostic risk factors of recurrence-free survival (RFS), metastasis-free survival (MFS), cancer-specific survival (CSS), and overall survival (OS) outcomes in patients with non-metastatic renal cell carcinoma (nmRCC) after curative nephrectomy during long-term-follow-up. The medical records of 4260 patients with nmRCC who underwent curative nephrectomy between 2000 and 2012 from five Korean institutions and followed-up after postoperative 1-month until December 2017 were retrospectively analyzed for RFS, MFS, OS, and CSS. During the median 43.86 months of follow-up, 342 recurrences, 127 metastases, and 361 deaths, including 222 cancer-specific deaths, were reported. In addition to the unreached median survival of RFS and MFS, the median OS and CSS times were 176.75 and 227.47 months, respectively. Multivariablte analyses showed that nephrectomy type (laparoscopy vs. open), pathological T stages, and nuclear grade were common significant risk factors for survival, and the baseline ASA, hemoglobin, and pathological N stage were common factors only for RFS, OS, and CSS (p < 0.05). Further, tumor necrosis for MFS; platelet count, extent (partial vs. radical) of surgery, and lymphovascular invasion for RFS; baseline diabetes, hypertension, age, body mass index, extent of surgery, and pathological sarcomatoid differentiation for OS; and baseline diabetes, hypertension, body mass index, and pathological sarcomatoid differentiation for CSS were additionally significant risk factors (p < 0.05). RFS, MFS, OS, and CSS were significantly different depending on the pathological T stages (p < 0.05). In conclusion, this large-numbered, long-term follow-up study revealed significant factors affecting the survival of patients with nephrectomized nmRCC.